Predominio de factores humanos o edáficos como determinantes de las etapas serales en el matorral estepario de una zona antropizada - Serrano M.; Bellot J.; Aguinaco M.T. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
This study shows a description of the present state of spontaneous shrubs developed on a non-cultivated surface in an irrigation area. The studied area is located on a gypsum soil subjected to intense agricultural and cattle use. Shrub formations reflect a transformation process from less altered situation to situation with a maximum alteration. The different phases are represented by communities with calcicole-gypsicole characteristics and nitrohalofile communities respectively. The latter occupy the points with the highest degree of disturbance.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)